PEDAGOGICAL CONDITIONS FOR DEVELOPING THE PHYSICAL FITNESS OF SPORTS SCHOOL STUDENTS BASED ON A SYSTEMATIC APPROACH (ON THE EXAMPLE OF FOOTBALL) - Xolmatov Nizomjon Umarjonovich (International Scientific and Current Research Conferences, 2025)
The article examines the set of pedagogical conditions that determine the effectiveness of physical-fitness development among students of specialised sports schools when a systematic approach is applied to football training. The study combines a longitudinal experiment with mixed-methods analysis over a two-year period and involves 124 male players aged 12–14 at the Olympic Reserve Football School in Tashkent. Quantitative monitoring of speed, strength, endurance and coordination indicators is complemented by qualitative observation of the instructional process, teacher–athlete interaction and learning climate. The data reveal that a carefully calibrated interplay between a structured curricular framework, differentiated workload allocation, continuous feedback through digital monitoring tools and an educational environment that integrates psychological support leads to statistically significant improvements across all motor components compared with the control cohort following a traditional programme. The discussion situates these findings within contemporary theories of systemic pedagogy and talent development, demonstrating how holistic design principles help overcome the fragmented nature of typical youth coaching. Recommendations are provided for policy makers and practitioners seeking to modernise sports-school curricula and harmonise athletic progress with long-term educational goals.